The Effect of Additional Effective Microorganisms in Vegetative Growth of Aerobic Paddy. Issue 1 (April 2021) - Shahbuddin, M; Shahbuddin, D; Amirullah, N; Syed-Azmi, S M S; Abdul-Rahman, S M
Abstract: The influence of effective microorganisms (EM), microbial inoculant containing yeasts, fungi, bacteria and actinomycetes was evaluated in field trials of Aerob 1 paddy cultivation in Jasin, Melaka. Aerobic paddy is a new way of rice cultivation in areas where water resources have been scare and affected by the climate change. As water shortage and climate change is becoming severe, the technology of growing rice with aerobic rice systems need to be further refined or developed to ensure the quality of rice production in water-short areas. The objective of this study was to determine the effect of additional EM on the growth pattern, and to evaluate the efficiency of EM uptake on the aerobic plant. This experiment was carried out by using random controlled Randomized Controlled Block Design (RCBD) consisted of three treatments with two replications in four blocks. Aerobic seed cv. Aeron1 was used as planting materials and has been applied by three different treatments of EM during vegetative growth. The treatment for this study was T1 = 1.8 g NPK with urea (control) while T2 was 1.8 g NPK and T3, with 0.9 g NP with 100 mL of EM respectively during 15 (early vegetative stage) and 45 DAS (late vegetative stage). The RCBD experimental design was used with two replications in each treatment in four blocks. There are three series of harvesting (35, 50 and 60 DAS) was conducted throughout this study. The growth parameter studied was shoot and root dry biomass, number of tillers, RGR at each of harvesting. Our finding revealed that the application of EM did not improve plant growth parameter but the growth pattern of T2 and T3 showed steady improvement, although not significant compared to T1. The application of EM at different growth stages did not enhance the relative plant growth rate of Aeron 1 under aerobic condition, but in comparison to T1 and T2, T3 treatment with 50% reduction of NPK and EM could significantly reduce the cost of land management and fertilizer.